B4-5: Neighborhood Deprivation and Telomere Length: Preliminary Findings from the Kaiser Permanente Research Program on Genes, Environment, and Health (RPGEH) - Van Den Eeden, Stephen (Marshfield Clinic, 2013)
BACKGROUND/AIMS: Shortened telomeres have been associated with numerous adverse health outcomes. In addition, a number of environmental or external exposures, including smoking, air pollution and stress, have been reported to be associated with short telomeres. We sought to examine how neighborhood quality of participants in the RPGEH Genetic Epidemiology Research Study on Adult Health and Aging (GERA) cohort affected telomere length. METHODS: The GERA cohort is a multi-ethnic cohort (average age = 63 years) of over 100,000 individuals with linked electronic medical records and questionnaire data. Telomere length was determined from a saliva sample in the Blackburn Laboratory using the novel Automated Telomere Length Analysis System (ATLAS) to handle the required high throughput processing of samples. Each sample was assayed six times using qPCR. Relative telomere length (T/S) was obtained from the initial concentrations of the sample telomere (T) with the corresponding sample reference gene (S). The distribution of (T/S) was found to be positively skewed and a log transformation was used to normalize the distribution. The final telomere length end point was the difference in adjusted means of telomere length per standard deviation unit by accounting for age and gender. The NDI is a standardized composite score of neighborhood quality derived from eight 2000 US Census data variables related to poverty/income, occupation, family structure, education and unemployment and normalized to a 100-point scale at the block-group level. RESULTS: A higher NDI indicates greater neighborhood deprivation. The NDI was linked with residential address at time of sample collection. We observed a pattern of shorter telomere length with increasing level of neighborhood deprivation. The pattern persisted even after accounting for age, gender, race/ethnicity, smoking, BMI, and the presence of cardiovascular disease, diabetes and other comorbidity. CONCLUSIONS: Our results suggest that neighborhood can adversely impact telomere length. Future plans will be discussed.